Impact of two organic fertilizers (mycorhize and poultry manure) associated with pollinators insects on growth and yields of Zea mays L. at Baré (Littorale Region-Cameroon) - Rodolphe, NGUEADJEU Audrey; DOUNIA; DOUKA , Chantal; Emmanuel, YOUMBI (JOURNAL OF ADVANCES IN AGRICULTURE, 2025)
Field of maize was conducted during the rainy season in 2021 and 2022 in Baré (Littorale Region - Cameroon) aiming to contribute to the improvement of the yield of maize by combining two organic fertilizers and pollinators insects. The main factor was pollination with two levels (plants left on free pollination and plants isolated from insects). The secondary aspect was fertilization with four points, mycorhize-poultry manure, mycorhize, poultry manure and control. The growth parameters, the diversity and foraging activity of pollinators insects, the influence of organic fertilizers and pollinator insects were evaluated on the yields. The results showed that the plants located on the plots treated with mycorhize-poultry, mycorhize and poultry manure showed significant growth on the number of the leaves (p<0.05) and collar diameter (p<0.05). In both years, a total of four orders of pollinator insects have been identified where Hymenoptera (90.94%) ranks first followed by Diptera (8.71%). Those insects harvested pollen (100%). Mean number of seeds per ears and the normal seeds left on free pollination was greater compared to those isolated from insects (p<0.001). The production (normal seeds and the mean number of seeds per ears) varies to 36.41 to 41.72 % in the plots having mycorhize-poultry manure, to 32.94 to 38.32 % plots having mycorhize and to 30.89 to 31.06 % to poultry manure plots associated with pollinators insect respectively. The use of organic manure especially the mycorhize-poultry manure and the maintenance of pollinators insect nest around the field mays by recommended to improve crop yield.